Coseismic slip and afterslip of the 2015 Mw 8.3 Illapel (Chile) earthquake determined from continuous GPS data. Issue 20 (28th October 2016) - Shrivastava, Mahesh N.; González, Gabriel; Moreno, Marcos; Chlieh, Mohamed; Salazar, Pablo; Reddy, C. D.; Báez, Juan Carlos; Yáñez, Gonzalo; González, Juan; de la Llera, Juan Carlos
Abstract: We analyzed the coseismic and early postseismic deformation of the 2015, Mw 8.3 Illapel earthquake by inverting 13 continuous GPS time series. The seismic rupture concentrated in a shallow (<20 km depth) and 100 km long asperity, which slipped up to 8 m, releasing a seismic moment of 3.6 × 10 21 Nm ( Mw = 8.3). After 43 days, postseismic afterslip encompassed the coseismic rupture. Afterslip concentrated in two main patches of 0.50 m between 20 and 40 km depth along the northern and southern ends of the rupture, partially overlapping the coseismic slip. Afterslip and aftershocks confined to region of positive Coulomb stress change, promoted by the coseismic slip. The early postseismic afterslip was accommodated 53% aseismically and 47% seismically by aftershocks. The Illapel earthquake rupture is confined by two low interseismic coupling zones, which coincide with two major features of the subducting Nazca Plate, the Challenger Fault Zone and Juan Fernandez Ridge. Key Points: Coseismic slip of the 2015 Illapel earthquake from cGPS data occurred in a highly locked interseismic region Postseismic afterslip following the Illapel earthquake The Challenger Fault Zone (CFZ) and the Juan Fernandez Ridge (JFR) played the role of barrier to seismic rupture